Museum Project: 14 Henrietta St. Museum, Paula Meehan, Dragana Jurišić and the Irish Housing Crisis - Kruczkowska, Joanna (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The aim of the article is to compare three (re)creative activities within one interdisciplinary project: a public space (14 Henrietta St. Museum in Dublin), poetry (Paula Meehan’s cycle of sonnets in Museum of 2019) and photography (Dragana Jurišić’s photos in the same book). They are all examined in the light of the current housing crisis in Ireland, which followed the collapse of the Celtic Tiger in 2008. The Museum project not only comments on the crisis and the changing social relations in Ireland but also challenges the perception of history and private/public memory. In the article, the components of the project are situated against biographical and historical backgrounds, and within the framework of new museology, memory studies, and the functions of photography and poetry.